Utilization of Barracuda Fish (Sphyraena barracuda) as fish nugget in Sorkam District, Central Tapanuli - Rosmasita Rosmasita; Tengku Muhammad Ghazali; Dian Fitria Manurung; Emma Suri Yanti Siregar; Irwan Limbong; Filla Simanjuntak; Hensamuel Situmeang (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Barracuda Fish in the Central Tapanuli region is known as Teter Fish (Sphyraena barracuda) which is still relatively cheap and easy to get throughout the year. Teter fish has many health benefits, but not everyone likes this fish. Based on this, various processed forms are needed in order to attract other people to continue consuming tethered fish. One of these processed forms is fish nuggets. The purpose of this community service activity is to provide education to the community, especially mothers in the Indonesian Family Welfare Guidance Program or PKK in Sorkam District, Central Tapanuli Regency about the use of Teter Fish meat as a processed material for making fish nuggets. The method used is the delivery of material and direct practice in making fish nuggets. The result of this community service activity is the ability of PKK women to make processed fish nuggets and package the product properly. In the future, fish nuggets can increase family income and are sold as a typical food of Central Tapanuli.